Circulating level of pigment epithelium-derived factor is associated with vascular function and structure: A cross-sectional study. (15th December 2016) - Kajikawa, Masato; Maruhashi, Tatsuya; Iwamoto, Yumiko; Iwamoto, Akimichi; Oda, Nozomu; Kishimoto, Shinji; Matsui, Shogo; Aibara, Yoshiki; Hidaka, Takayuki; Kihara, Yasuki; Chayama, Kazuaki; Goto, Chikara; et al.
Abstract: Background: Pigment epithelium-derived factor (PEDF) is a glycoprotein that belongs to the superfamily of serine protease inhibitors. It is thought that PEDF plays a protective role against atherosclerosis. Clinical studies have shown that serum levels of PEDF are increased in subjects with cardiovascular risk factors. The role of PEDF in cardiovascular disease is still controversial. The purpose of this study was to evaluate the associations between serum levels of PEDF and vascular function and structure. Methods: We measured serum levels of PEDF, assessed vascular function by measurements of flow-mediated vasodilation (FMD) and nitroglycerine-induced vasodilation in the brachial artery, and measured brachial artery intima-media thickness (IMT) in 150 subjects who underwent health examinations. Results and conclusions: Univariate regression analysis revealed that serum level of PEDF was significantly correlated with body mass index, high-density lipoprotein cholesterol, glucose, FMD, nitroglycerine-induced vasodilation, and brachial artery IMT. Multivariate analysis revealed that serum levels of PEDF remained an independent predictor of nitroglycerine-induced vasodilation (β = − 0.20, P = 0.02) and brachial artery IMT (β = 0.14, P = 0.03) after adjustment of cardiovascular risk factors, while serum level of PEDF was not associated with FMD (β = − 0.02, P = 0.79). These findings suggest that PEDF may be a factor directly associated with atherosclerosis. The serum level of PEDF may be a new biochemical marker of atherosclerosis. Highlights: PEDF was significantly correlated with vascular function and structure. Serum PEDF level was an independent predictor of NID and brachial artery IMT. Serum PEDF level was not associated with FMD after adjustment of confounders. PEDF might work as anti-atherosclerotic counter-system to advanced atherosclerosis. Serum level of PEDF may be a new biochemical marker of atherosclerosis.